The coronavirus disease 2019 pandemic among adult congenital heart disease patients: findings of a one-year multicentric, international study. (14th October 2021) - Ruperti Repilado, F J; Greutmann, M; Bouchardy, J; Brennan, P; Campens, L; Gallego, P; Garcia-Orta, R; Jensen, A S; Ladouceur, M; Miranda-Barrio, B; Morissens, M; Rueda Soriano, J; et al.
Abstract: Introduction: One year after the beginning of the Coronavirus Disease 2019 (COVID-19) pandemic, the evidence on outcomes among adults with congenital heart disease (ACHD) is still limited. Purpose: We aimed to compare patient characteristics and outcomes between the first and the subsequent COVID-19 waves and to identify overall predictors for complicated disease course among ACHD patients. Methods: We collected reported COVID-19 cases among ACHD patients followed at 26 tertiary care centers in 10 European countries between March 27, 2020 and March 25, 2021. Patient characteristics, heart defect complexity and residual problems, medical history, date of diagnosis and course and outcome of COVID-19 were recorded. Cases were stratified into first vs. subsequent COVID-19 waves (cut-off date July 15, 2020). A complicated disease course was defined as hospitalization for COVID-19 requiring ventilation and/or inotropic support, extracorporeal membrane oxygenation or death. Data were reported as median (interquartile range) and counts (percentage). Results: Overall, 548 cases were included (first wave: n=161; subsequent waves: n=387). Median age 33 (26–44) years, 52% female. Thirty-three patients (6%) had a complicated disease course. Between waves (first vs. subsequent), there were no statistically significant differences related to gender (women 57% vs. 49%, p=0.09), body mass index (BMI) category (p=0.7), heart defect complexity (p=0.08) and residual heart defect-related problems (p=0.6). Patients in the first wave were older, had more often ≥2 comorbidities and a complicated disease course (37 vs 33 years, p=0, 001; 17% vs. 7%, p=0.0003; and 9% vs. 5%, p=0.04, respectively). The proportion of deaths did not significantly differed between waves (4% vs 2%, p=0.2). A detailed comparison of the above-reported characteristics is depicted in table 1. From multivariable models, adjusted odds ratios (OR) (95% confidence interval) for the prediction of complicated COVID-19 course are depicted in table 2. Main independent predictors for a complicated disease course were: cyanotic heart disease, including unrepaired cyanotic defects or severe pulmonary hypertension with Eisenmenger syndrome (OR 8.49 [3.14–22.94], p<0.001), BMI >25 kg/m 2 (OR 3.91 [1.62–9.43], p=0.002), having ≥2 comorbidities (OR 2.63 [1.05–6.62], p=0.04) and age per five years (OR 1.21 [1.05–1.42], p=0.01). Conclusion: Complicated COVID-19 course among ACHD patients is rare. Outcomes in the first wave were worse when compared to subsequent waves, mainly because patients of the first wave were older and had more comorbidities. Age, cyanotic heart disease (including unrepaired cyanotic defects or severe pulmonary hypertension with Eisenmenger syndrome), having ≥2 comorbidities and a BMI >25 kg/m 2 were the main predictors for a complicated disease course. Funding Acknowledgement: Type of funding sources: None.